2002
DOI: 10.1039/b205242c
|View full text |Cite
|
Sign up to set email alerts
|

1H NMR spectroscopic and thermodynamic studies of hydrogen bonding in liquid n-butanol + cyclohexane, tert-butanol + cyclohexane, and n-butanol + pyridine mixtures

Abstract: H NMR chemical shifts d OH of the proton in the hydroxyl group of n-butanol and tert-butanol have been measured as function of mixture composition in the binary mixtures n-butanol + cyclohexane, tertbutanol + cyclohexane, and n-butanol + pyridine at 303, 313 and 323 K. In addition the molar excess enthalpy H E of n-butanol + pyridine has been determined as a function of the mixture composition at 298 K using a flow calorimeter. The ERAS (extended real associated solution) model has been applied for describing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 38 publications
(53 reference statements)
1
26
0
Order By: Relevance
“…4. Implementation of the association into the theoretical treatment of the Kirkwood factor g K The ERAS-model [29][30][31][32][33][34][35][36][37] combines a chemical association model based on the Flory-Huggins theory for polydisperse multimers with an equation of state for flexible molecules of different size and their mixtures. In order to derive Kirkwood factors g K the chemical association involved into the ERAS-model has to be accounted for.…”
Section: It Holdsmentioning
confidence: 99%
See 2 more Smart Citations
“…4. Implementation of the association into the theoretical treatment of the Kirkwood factor g K The ERAS-model [29][30][31][32][33][34][35][36][37] combines a chemical association model based on the Flory-Huggins theory for polydisperse multimers with an equation of state for flexible molecules of different size and their mixtures. In order to derive Kirkwood factors g K the chemical association involved into the ERAS-model has to be accounted for.…”
Section: It Holdsmentioning
confidence: 99%
“…Since we are dealing with the simultaneous description of g K and the molar excess enthalpy H E m of alcohol + pentane and alcohol + hexane mixtures in this work the expression of the ERAS-model for H E m already derived in our previous work 36…”
Section: It Holdsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of hydrogen bond formation in aliphatic alcohols have been carried out with different experimental methods, for example, vapor pressure [3,4] and calorimetric measurements [5][6][7][8], infrared (FTIR) spectroscopy [9][10][11][12][13][14] and nuclear magnetic resonance (NMR) [15][16][17][18][19] techniques. The authors attempted to solve two major tasks in these studies.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, spectroscopic investigations of model systems as CO2-alkanol on thermodynamic and molecular dynamic background represent a current research area. Thus far CO2-methanol fluids, a scientifically interesting and a technologically important class of mixed solvents have enjoyed the most attention, and a number of authors have reported vibrational spectroscopy [20][21][22][23] , NMR spectroscopy [24][25][26][27][28][29][30][31] , absorption and emission spectra 13 as well as molecular dynamics simulation 14 on such systems. Meanwhile, NMR spectroscopy is regarded as a very informative method to probe the properties of fluids on a microscopic level, and NMR spectroscopy at NCFs/ SCFs conditions also has potential applications in the studies of hydrogen bonds or reaction monitoring 24 as molecular structural changes induced by pressure on hydrogen bonds are also very interesting topics.…”
Section: Introductionmentioning
confidence: 99%